De Nederlandse zeeschilderkunst in de negentiende eeuw - Bosman, Cécile (Amsterdam University Press, 2024)
Marine painting, paintings of ships and the sea, is a four hundred year old traditional Dutch art discipline. In the nineteenth century the genre had a special artistic prestige and status. This study explores the background, training, studio practice, stylistic development and subject matters of the Dutch nineteenth-century marine painter. A Reference List of Marine Painters, which is a new overview of the true specialists in the genre in this period, is added. The key question is how marine painting was looked at by the marine painters themselves, their fellow painters at the artists associations, in art theory and in art criticism. It turns out that within Dutch art circles throughout the nineteenth century, marine painting was perceived as a bearer of national pride. By placing the genre in a broader cultural-historical context it reveals how marine painting, together with the glorification of maritime history, was embedded in nationalist ideology.